PROMOTION OF EMBRYOS GROWTH FOR IN VITRO CULTURED SEEDS OF LOCAL Citrus limon L. BRUM. F. - Ammar Zeki Kassab-Bashi (Mesopotamia Journal of Agriculture)
In this study seeds of local lemon were cultured in solidified Murashige and Skoog medium in order to examine the effect of combining Benzyladenine (BA) and Kinetin (Kin), in different concentration on the growth of embryos with / without seed coat. Favorable results were obtained after 6 weeks from seeds without seed coat comparably with seeds with seed coat, embryos growth from seeds without seed coat was in different degrees, were as, optimum results obtained in treatment containing Kin alone 3mg/L, average number of seedling from each seed 2.6 compared with 1.75 of control treatment (completely without cytokinins). The individual or combined use of BA and Kin caused increasing seedling steam length of seeds without seed coat compared with control treatment, while increasing root length when treated with Kin alone at concentration of 3mg/L .The subsequent use of BA and Kin at concentration of 2.5+0.5 mg/L caused elongation highest number of lateral buds of seedling which 2.29. When highest number of adventitious bud (80 %) occurred in treatment seeds without seed coat containing BA and Kin at concentration 1.5 mg/L for each one that was 2.13 buds from every seed.